Satisfaction of dysphonic patients with psychosomatic assessment and intervention Zufriedenheit dysphoner Patienten mit einer psychosomatischen Diagnostik und Intervention - Puelz, S.; Schützenberger, Anne; Grässel, Elmar; Koellner, V.; Eysholdt, Ulrich; Rosanowski, Frank (HNO, 2009)
Background: Comorbid physical and psychological complaints are more common in patients with dysphonia than in the general population. In a prospective randomized study the effects of structured psychosomatic diagnostics and verbal intervention on the satisfaction of patients with dysphonia were investigated. Materials and methods: A total of 54 dysphonic patients (33 women, 21 men, age 51.1±16.4 years) with dysphonia (organic n=36, functional n=18) were examined and their subjective experiences were collected by the following psychometric questionnaires: voice-related quality of life (VRQOL), hospital anxiety and depression scale (HADS-D) and the "Gießener Beschwerdebogen" (Gießen questionnaire on physical complaints GBB). Patients were randomized into 2 groups: group 1 (n=27) filled in the questionnaires and the answers were reviewed within the medical consultation. This was followed by an interview on patient satisfaction. In the control group 2 (n=27) a medical examination and consultation were carried out and then questioned on patient satisfaction. The psychometric questionnaires were completed by the patients shortly before leaving the department. Results: The study group 1 was significantly more satisfied than group 2 on different statistic levels according to the items compared. Conclusions: Patients suffering from dysphonia are positively influenced with respect to patient satisfaction by a structured psychosomatic diagnostic and intervention. © Springer Medizin Verlag 2009.
CRIS-Team Scopus Importer:2022-09-20
Keywords: Dysphonia; Gießen questionnaire on complaints; Patient satisfaction; Psychosomatics; Voice-related quality of life (VRQOL)